On the optical properties of the nonideal plasma of electrical pulse discharge in water - Starchyk, P.D.; Porytskyy, P.V. (Вопросы атомной науки и техники, 2007)
It is shown that the most important influence on the plasma of electrical pulse discharges in liquid have the processes in a zone of its contact with condensed medium. The optical properties of a channel plasma are considered through the opacity of the layer. The properties are calculated on the base of microfield theory of non-ideal plasma. Розглянуто вплив процесів у примежовому шарі між густою неідеальною плазмою електричних розрядів у воді та оточуючим середовищем. Показано, що випромінювання плазми розряду екранується в примежовому шарі внаслідок процесів збудження та іонізації. Оптичні властивості плазми розряду розглядаються на основі мікропольової теорії неідеальної плазми. Рассмотрено влияние процессов в пристеночном слое между плотной плазмой импульсных разрядов в воде и внешней средой. Показано, что излучение плазмы разряда экранируется в переходном слое вследствие процессов возбуждения и ионизации. Оптические свойства плазмы разряда рассматриваются на основе микрополевой теории неидеальной плазмы.